Xylem sap phosphorus sampling using microdialysis-a non-destructive high sampling frequency method tested under laboratory and field conditions - Jeřábek, Jakub; Rinderer, Michael; Gessler, Arthur; Weiler, Markus (Tree physiology, 2020)
For a better understanding of plant nutrition processes, it is important to study the flux of nutrients within plants. However, existing xylem sap sampling methods are typically destructive and do not allow for repeated, highly frequent measurements of nutrient concentration. In this paper, we present a novel use of microdialysis (MD) for characterizing xylem sap phosphate (PO43-) concentration as a possible alternative to destructive sampling. First, MD probes were tested under laboratory conditions in vitro, in a stirred solution test, and in vivo, using beech tree stem segments. Exponential decline in the relative recovery (RR) with an increasing MD pumping rate allows for determining an optimal sampling interval (i.e., the maximum amount of sample volume with the minimum required concentration). The RR changed only minimally, with a change in the simulated sap flow velocity during the in vivo stem segment test. This suggests that MD can be applied over a range of naturally occurring sap flow velocities. Differences in the ionic strength between the xylem sap and the perfusate pumped through the MD did not influence the RR. Then, MD was successfully applied in a 24 h field campaign in two beech trees of different ages and allowed for in situ assessments of the diurnal variation of PO43- concentration and (together with xylem flow measurements) flux variability in living trees. Both beech trees exhibited the same diurnal pattern in PO43- concentrations with higher concentrations in the younger tree. The xylem PO43- concentration measured with MD was in the same order of magnitude as that received through destructive sampling in the younger tree. The MD probes did not show a decline in RR after the field application. We showed that MD can be applied to capture the PO43- concentration dynamics in the xylem sap with bihourly resolution under field conditions.
Keywords: mikrodialýza; laboratoře; stromy; microdialysis; in situ measurement; diurnal nutrition variability; phosphorus; Trees; Phosphorus; Xylem; xylém; xylem sap; Laboratories; Microdialysis; fosfor